2000
DOI: 10.1037/0735-7044.114.5.950
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive sequelae of infants of diabetic mothers.

Abstract: On the basis of animal models, it was hypothesized that infants of diabetic mothers (IDMs) would be at risk for suffering damage to the hippocampus primarily because of fetal iron deficiency, chronic hypoxia, and hypoglycemia. This, in turn, may result in impairments in recognition memory at a young age. To test this model, the memory of 6-month-old IDMs and control infants was evaluated with electrophysiological (event-related potential [ERP]) and behavioral (looking time) measures. At 12 months, the Bayley S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(127 citation statements)
references
References 25 publications
6
118
0
3
Order By: Relevance
“…2,5 Children of diabetic pregnancies may also experience disturbed cognitive development and recognition memory, consistent with a hippocampal insult. 6,[9][10][11][12]24 The fetal hippocampus is targeted by hypoxia-ischemia, impaired iron delivery and postnatal hypoglycemia, all of which accompany poorly controlled diabetes during pregnancy. 11,12,25 In diabetes, specific defects in placental function are unable to compensate for increased iron needs accompanying fetal overgrowth and increased erythrocyte mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5 Children of diabetic pregnancies may also experience disturbed cognitive development and recognition memory, consistent with a hippocampal insult. 6,[9][10][11][12]24 The fetal hippocampus is targeted by hypoxia-ischemia, impaired iron delivery and postnatal hypoglycemia, all of which accompany poorly controlled diabetes during pregnancy. 11,12,25 In diabetes, specific defects in placental function are unable to compensate for increased iron needs accompanying fetal overgrowth and increased erythrocyte mass.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recent work shows that long-term cognitive deficits in offspring of women with poorly controlled diabetes are similar to those seen in tissue iron deficiency. [9][10][11][12] The erythrocyte zinc protoporphyrin/heme (ZnPP/H) ratio measures inadequate erythrocyte iron incorporation. Heme is synthesized from iron and protoporphyrin IX.…”
Section: Introductionmentioning
confidence: 99%
“…However, 2 studies 35,36 were further excluded because they were published with the same populations used in 2 included studies. 18,20 In addition, 5 relatively different studies 22,32,[37][38][39] were conducted by using the same cohort study with varied sample sizes. All reported global cognitive development as a secondary outcome or confounder at the age of 1 year 32, 37-39 and 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, mixed results have been reported, with null or positive associations between different measures of maternal metabolic control and diverse measures of cognitive ability. 26,29,33,39 Even with well-controlled maternal diabetes, offspring's cognitive development has been found to be significantly impaired. 19,31 Regardless of maternal metabolic control, in our systematic review, 1 study 16 fully adjusted for potential confounders with relatively good power, as well as other studies 19,21,[29][30][31][32][33] that partially adjusted for potential confounders, reported significantly impaired cognitive development in offspring born to mothers with either PDM or GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the adverse effects of diabetic pregnancy on the developing brain including neurobehavioral deficits in both sensory-cognitive and psychomotor functions, such as altered auditory recognition memory processing at birth (Siddappa et al, 2004), reduced visual and memory performance at 8 and 12 months (DeBoer et al, 2005), poorer performance on tests of general development in infants and toddlers and inferior performance in elementary school children (Ornoy, 2005), motor delay may be a sign of mild, nonspecific brain damage and the abnormalities in memory processing (Nelson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%